TIR‐domain‐containing adapter‐inducing interferon‐β (TRIF) forms filamentous structures, whose pro‐apoptotic signalling is terminated by autophagy. (19th May 2017) - Gentle, Ian E.; McHenry, Kevin T.; Weber, Arnim; Metz, Arlena; Kretz, Oliver; Porter, Dale; Häcker, Georg
Abstract : The formation of amyloid‐like protein structures has recently emerged as a feature in signal transduction, particularly in innate immunity. These structures appear to depend on defined domains for their formation but likely also require dedicated ways to terminate signalling. We, here, define the innate immunity protein/Toll‐like receptor adaptor TIR‐domain‐containing adapter‐inducing interferon‐β (TRIF) as a novel platform of fibril formation and probe signal initiation through TRIF as well as its termination in Toll‐like receptor 3 (TLR3)‐stimulated melanoma cells. A main signalling pathway triggered by TLR3 caused apoptosis, which was controlled by inhibitor of apoptosis proteins and was dependent on RIPK1 and independent of TNF. Using correlative electron/fluorescence microscopy, we visualised fibrillar structures formed through both Toll/interleukin‐1 receptor and RIP homotypic interacting motif regions of TRIF. We provide evidence that these fibrillary structures are active signalling platforms whose activity is terminated by autophagy. TRIF‐signalling enhanced autophagy, and fibrillary structures were partly contained within autophagosomes. Inhibition of autophagy increased levels of pro‐apoptotic TRIF complexes, leading to the accumulation of active caspase‐8 and enhanced apoptosis while stimulation of autophagy reduced TRIF‐dependent death. We conclude that pro‐death signals through TRIF are regulated by autophagy and propose that pro‐apoptotic signalling through TRIF/RIPK1/caspase‐8 occurs in fibrillary platforms. Abstract : Toll/interleukin‐1 receptor‐domain‐containing adapter‐inducing interferon‐β (TRIF) is recruited to both TLR3 and TLR4 and can induce cell death as well as cytokine responses. Here, we show using correlated fluorescence and electron microscopy that TRIF forms fibrillar signalling platforms inside cells when activated and that these platforms are targeted by autophagy for degradation. Inhibition of autophagy results in enhanced pro‐apoptotic signalling and cytokine production in Melanoma cells.